PERSPEKTIF EKONOMI ISLAM PADA PENGOLAHAN LIMBAH PLASTIK (STUDI PADA SISTEM PRODUKSI DI UD. WAHYU PLASTIK) - Muhammad Turmudi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
This research aims to investigate the business model of plastics recycling at UD. Wahyu Plastik based on Islamic economics perspective. This research uses descriptive qualitative method. The data is collected by observation, interview and document study. The results indicate that production factors: the land as a place of business is a privately owned by business owners, labor is positioned in place accordance with the needs of production, so there is no wastage of employees' wages, private capital and proceeds derived from bank loans, management functions apply to all stages of production, the raw materials, used plasctics, purchased from suppliers with the price of both sides agree. Plastics recycling of UD. Wahyu Plastik is limited to grinding the plastics into small pieces not yet ready for pellets/plastics seeds production or ready-made products. The recycling prosess is conducted through some stages: separating raw materials by type and color; cleaning and washing; milling of raw materials; drying of the mill; packing the dried mill into the sack. Palstics recycling business opportunity is formed due to the mutual effort of the collectors, plastics waste processors and manufacturers of finished products.